Taste‐Based Discrimination, Tolerance and the Wage Gap: When Does Economic Freedom Help Gay Men?. (25th March 2019) - Christafore, David; Leguizamon, Susane
Summary: Although gay men have reported experiencing labor market discrimination, re‐ search studies on a potentially discriminatory wage gap have reported mixed findings. We consider the Becker model of taste based discrimination which hypothesizes that we will observe, in the presence of discrimination, a smaller or non‐existent wage gap in more competitive markets. Using economic freedom at the state level as a measure of market competitiveness, and controlling for other influential characteristics, we analyze the wages of over 300, 000 men in the United States to consider how economic freedom influences the wage gap between cohabitating gay men and married straight men be‐ tween the years 2000 and 2014. We find evidence consistent with model predictions in the presence of labor market discrimination for the states in the South and regions with the highest concentrations of religious households but not in the Northeast, West and less religious regions. Given the lower levels of public support of gay rights in the South and religious regions, this result suggests that gay men may be experiencing la‐ bor market discrimination in these regions but not in regions which typically offer more public support. These findings may help reconcile contradictory findings in previous research which did not explicitly allow for differential regional and religious influences.